Overexpression of GmGAMYB Accelerates the Transition to Flowering and Increases Plant Height in Soybean - Yang, Xue; Li, Xin; Shan, Jinming; Li, Yinghua; Zhang, Yuntong; Wang, Yuhe; Li, Wenbin; Zhao, Lin (Frontiers in Plant Science, 2021)
The flowering time and plant height of soybean are important agronomic characters, which control the adaptability and yield of soybean. R2R3 MYB transcription factor plays an important regulatory role in plant growth and development. In this study, soybean GmGAMYB gene of R2R3-MYB type was induced by long-days (LDs). GmGAMYB showed higher transcriptional levels in the flowers, leaves and pods of soybean. Overexpression of GmGAMYB in transgenic soybean showed earlier flowering time and maturity in LDs and short-days (SDs). GmGAMYB interacted with GmGBP1 and might promote flowering time by up-regulating the expression of GmFULc gene in soybean. Moreover, the expression level of GmGAMYB was also induced by gibberellins (GAs) and the plant height of GmGAMYB-ox plants was significantly increased, which was caused by the enlargement of internode cell in stem. Furthermore, GmGAMYB overexpression led to increased GA sensitivity in the hypocotyl of soybean seedlings compared with WT. GmGAMYB may be a positive regulator of GA response of promoting plant height by up-regulating the expression of GmGA20ox gene in soybean. Together, our studies preliminarily showed that the partial functions of GmGAMYB in regulating flowering time and GA pathway.